COSO: ENTERPRISE RISK MANAGEMENT SEBAGAI UPAYA MEMPERTAHANKAN KEBERLANGSUNGAN PERUSAHAAN JASA TRAVEL HAJI DAN UMRAH - Muhammad Rizieq Fadilah; Novita Novita (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
This study was conducted to see whether there is an influence of Enterprise Risk Management (ERM) in maintaining business continuity in the Hajj and Umrah travel service business due to the closing of the Hajj and Umrah departure gates in 2020 and 2021 due to the Covid-19 pandemic. The object of this research is Jasa Daqu Travel, one of the providers of Hajj and Umrah travel services in Indonesia. Data processing methods are descriptive analysis and verification analysis using the Partial Least Square method using SMART-PLS Software. The sample used is all employees of Jasa Daqu Travel. The results of this study are Enterprise Risk Management (ERM) has the effect of being able to maintain the continuity of the Daqu Travel Services business by implementing the internal environment, goal setting, event identification, risk assessment, risk response, control activities, information and communication and supervision. The implication of this research is that Daqu Travel Services as a provider of Hajj and Umrah Travel Services in the future can maintain its business continuity during the Covid-19 pandemic by continuing to implement Enterprise Risk Management. Keywords: Enterprise Risk Management; Going Concern; Hajj and Umrah Travel